MENGEMBANGKAN NILAI MORAL DAN DISIPLIN AUD MELALUI METODE BERCERITA - Ema Fatmawati; Ema Huzaimah; Heni Nafiqoh (IKIP Siliwangi, 2018)
moral is habit that every individual does both good and bads morals.The abudance of poor children’s behaviors in the present is very worrying, lack of manners and lack of discipline in the lives of chidren now, while they are the nation’s future candidates As our teachers and parents have very important task in instilling moral education and discipline to children starting from early childhood, with creating a learning system that is fun and can be acceptable to children but can teach about moral messages and discline. thourgh storytelling there are many moral messages that can be conveyed to the child, including good character messages , imagination education, and can build emotional closeness between teachers and children, so that the development of moral attitude and good discipline can be formed from early childhood.